Conflicting Interests in Multi-Species Catch Quota Share Fisheries Regimes - Már Kristjónsson 1985- (2011)
In this thesis a potential conflict of interest is examined in multi-species fisheries, managed under a catch quota share system, where stocks are interdependent. A theoretical model is presented and the optimal harvest strategies for individual harvesters analyzed and compared with the socially optimal harvest strategies. The results of the analysis is that the management strategy that maximizes the profit of an individual harvester is different from the strategy that maximizes the profits of another if their catch quota share holdings are differently distributed for harvested stocks. The cod and capelin fisheries of Iceland are examined to see whether they correspond with the model. Cod and capelin are interrelated as the cod relies on the capelin as a food source. Therefore the profits from the cod fishery are affected by the harvest strategy for capelin. As most harvesters hold unevenly distributed catch quota shares for cod and capelin, it is reasoned that it is at least plausible that different harvest strategies would maximize the profits of different harvesters, as the model would imply.